Nova direção na Minas Transportes de Passageiros: percepções sobre a mudança organizacional - Linke, Daisy Selau Porto (2011)
This research analyzes some managers and their subordinates perceptions and attitudes on the process of organizational change occurred in a business of transporting passengers by bus on the guidelines outlined by the "new direction" of the company. Techniques of document review, semi-structured interviews and participant observation to the construction of field data are used in this study. Analysis of data built and tested by free association is qualitative and interpretive. After initial literature review, there is a mapping of old and new formal guidelines, set by the new directors, corporate hierarchy, perceptions and reactions of respondents named as new directors or chiefs, managers and their subordinates. Examples of professional careers, speech, management actions and their receiving by managers subordinates are described in order to enhance field analysis understanding. Interactions among new formal guidelines, management actions, perceptions and reactions of respondents in the face of changes within the organization are analyzed. The concept of organizational change is retrieved from Business Administration and expanded under the approaches of sociology and anthropology of which are taken the concepts of structure and agencies as a form of power. This paper concludes that perceptions of respondents reveal differences between speech and actions in the face of changes brought about by the constraint of the structure and agencies. The survey results indicate that analyzed agencies present alternate projects between forcing and resisting to organizational change.